Optimizing zinc supplementation levels of rainbow trout (Oncorhynchus mykiss) fed practical type fishmeal‐ and plant‐based diets. (2nd February 2015) - Welker, T.; Barrows, F.; Overturf, K.; Gaylord, G.; Sealey, W.
Abstract: Rainbow trout (23.1 ± 0.4 g) were fed either a fishmeal‐ or plant‐based diet supplemented with various levels of zinc (0, 15, 30, 60 or 120 mg kg −1 ) for 12 weeks. Trout fed the fishmeal diet had significantly higher weight gain than with the plant‐based diet. Zinc supplementation in the fishmeal diet had no effect on growth performance, suggesting that additional dietary supplementation of zinc is not required. However, in trout fed the plant‐based diet, growth increased significantly up to 30 mg kg −1 zinc after which growth was not affected. Trout fed the plant‐based diet containing no zinc exhibited severe growth retardation, and in fish fed the 0 and 15 mg kg −1 zinc diets, cataracts were present. Use of broken‐line quadratic modelling suggests that dietary supplementation of zinc needed to prevent deficiency and promote adequate growth in rainbow trout fed the plant‐based diet in this study was 30.1 mg kg −1 (80 mg kg −1 total dietary zinc). This is higher than the NRC (2011, Nutrient Requirements of Fish and Shrimp ) dietary recommended level of 15 mg kg −1 for rainbow trout. Following the NRC recommendation could lead to zinc deficiency in rainbow trout fed a plant‐based diet.